Racial and Ethnic Disparities in Infant Mortality in the United States: The Role of Gestational Age - Chen, Han-Yang; Chauhan, Suneet P.; Rankins, Nicole C.; Ananth, Cande V.; Siddiqui, Danish S.; Vintzileos, Anthony M. (American Journal of Perinatology, 2013)
Objective We assessed the association among gestational age (GA) at birth, timing of death, and risk status of the pregnancy and racial/ethnic disparities in infant mortality rate in the United States.Study Design We utilized U.S. 2000 to 2004 birth cohort–linked birth and infant death data restricted to nonanomalous singleton live births. Multivariable log-binomial regression models were fit to evaluate racial/ethnic disparities in infant mortality while adjusting for potential confounders.Results Compared with whites, blacks had a higher adjusted infant mortality rate (IMR) (risk ratio [RR] 1.96, 95% confidence interval [CI] 1.91, 2.01), and Hispanics had a lower adjusted IMR (RR 0.79, 95% CI 0.76, 0.82). When categorized by GA, at 24 to 31 weeks, the adjusted early neonatal mortality (ENM) is significantly lower for black than whites, similar at 32 to 36 weeks, and at 37 weeks or more, blacks have significantly higher ENM.Conclusions The racial/ethnic disparities in infant mortality in the United States persist and vary across GA. These disparities may largely be driven by the excess post-neonatal deaths among blacks.
Keywords: infant mortality; racial disparities; gestational age; high-risk pregnancy